2021
DOI: 10.1093/jxb/erab193
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thioredoxin m in chloroplasts alters carbon and nitrogen partitioning in tobacco

Abstract: In plants, there is a complex interaction between carbon (C) and nitrogen (N) metabolism and its coordination is fundamental for plant growth and development. In the present work, the influence of thioredoxin (Trx) m on C and N partitioning was studied using tobacco plants overexpressing Trx m from the chloroplast genome. The transgenic plants showed altered metabolism of C (lower leaf starch and soluble sugar accumulation) and N (with higher amounts of amino acids and soluble protein), which pointed to an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…It is a component of the main substances in crops, such as nucleic acid, protein, and chloroplast. 13 Nitrogen actively participates in a variety of physiological pathways, such as osmotic substance synthesis, 14 ROS scavenging, 15 photosynthesis regulation, 16 and so on. Ahanger et al 17 pointed out that nitrogen application could enhance the accumulation of antioxidant substances and osmolyte metabolism of wheat, and alleviate the growth inhibition caused by salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is a component of the main substances in crops, such as nucleic acid, protein, and chloroplast. 13 Nitrogen actively participates in a variety of physiological pathways, such as osmotic substance synthesis, 14 ROS scavenging, 15 photosynthesis regulation, 16 and so on. Ahanger et al 17 pointed out that nitrogen application could enhance the accumulation of antioxidant substances and osmolyte metabolism of wheat, and alleviate the growth inhibition caused by salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of N metabolism by TRX has been proven in tobacco overexpressing Trx m, which exhibited reduced production of starch and soluble sugar but increased amino acid and T A B L E 1 Reports showing role of "S" species in mitigating various abiotic stress responses. protein accumulation (Ancín et al, 2021). In rice, multiple OsTrx genes have been shown to respond to multiple environmental stresses (Nuruzzaman et al, 2012).…”
Section: Sulfur-containing Metabolites and Their Role Under Stressmentioning
confidence: 99%
“…TRX can also directly decrease ROS levels through the action of thioredoxin peroxidase (Yamawaki et al, 2003) and has been reported to play important roles in DNA and protein repair (Lu & Holmgren, 2014). Activation of N metabolism by TRX has been proven in tobacco overexpressing Trx m , which exhibited reduced production of starch and soluble sugar but increased amino acid and protein accumulation (Ancín et al, 2021). In rice, multiple OsTrx genes have been shown to respond to multiple environmental stresses (Nuruzzaman et al, 2012).…”
Section: Sulfur‐containing Metabolites and Their Role Under Stressmentioning
confidence: 99%
“…In this study, redox-related proteins also changed with the increase in row spacing. Additionally, observed redox-related proteins may be critical for maintaining the balance between C and N metabolism (Ancín et al, 2021). So, they could be good candidates for enriching the regulation network of light efficient utilization.…”
Section: Photosynthetically Active Radiation-use Efficiency Is Improv...mentioning
confidence: 99%